Eco Polymeric Materials and Natural Polymer (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint covers the latest developments in the field of eco-polymeric materials and natural polymer processing and utilization, highlighting cutting-edge research focusing on the processing of advanced polymers and their composites. It demonstrates that the field of eco-polymeric materials and natural polymers is still gaining increased attention. Innovative approaches as well as advanced applications of eco-polymeric materials and natural polymers in different fields, such as energy, environment, biomedical, biomaterial, and engineering, are reported in this reprint.